Influence of Interpersonal Conflicts on Teaching and Learning in Public Secondary Schools: A Case of Magu District, Mwanza – Tanzania - Mwidege, Vicent Alfredy; Tangi, Felista (International Journal of Humanities and Education Development (IJHED), 2021)
The purpose of the study was to assess influence of interpersonal conflict on teaching and learning in public secondary schools in Magu District. Mwanza; Tanzania. The objectives of the study were; to identify the types of interpersonal conflicts commonly found in public secondary schools, to examine the strategies employed by heads of schools in managing interpersonal conflicts and to explore the challenges faced by heads of schools in managing interpersonal conflict. The study was guided by Conflict Theory. The study employed mixed research approach and convergent parallel research design. Descriptive statistics was used to analyze quantitative data while qualitative data were analysed thematically. The targeted population was 1861 from whom the sample of 181 respondents were selected using purposeful and simple random sampling. Majority of the respondents said poor communication channel among teachers, the use of abusive language and names calling, scarcity of resources, indiscipline among students, corporal punishment to students and poor academic performance were the types of interpersonal conflicts between teacher-teacher and teacher – students in their schools. Nevertheless, the study discovered that heads of schools preferred negotiations, regular meetings, compromising, conferences, seminars and avoiding as the strategies for interpersonal conflict management. Furthermore, the study revealed most of heads of schools are not well trained on prior interpersonal conflict management. Therefore no specific strategies employed by heads of schools in managing interpersonal conflict in Magu district rather most of heads of school use their own experience in handling interpersonal conflicts